Restoring civil societies - Jonas, Kai J.; Morton, Thomas A. (Hoboken, New Jersey : Wiley-Blackwell, 2012)
"Restoring Civil Societies examines the role of civic engagement as a form of prosocial behavior motivated by a commitment to higher-order norms. Civic engagement--from bystander intervention to organizing collective activity--is distinguished as a collective effort by which individuals re-institute the civil basis of society in the wake of a social rupture, whether from war, natural disaster, or other causes. Restoring Civil Societies fills the gap between basic research on social issues and the translation into social policy or program interventions"--
"Focuses on different forms of civic engagement as an activity motivated by threatening intergroup contexts or a commitment to higher-order social norms"--
Introduction / Kai J Jonas, Thomas A Morton -- Theoretical Approaches. Justice Sensitivity as Resource or Risk Factor in Civic Engagement / Anna Baumert, Nadine Thomas, Manfred Schmitt -- Regulating Psychological Threat / Bastiaan T Rutjens, Joop van der Pligt, Frenk van Harreveld -- Prosocial Behavior in the Context of Crisis / Kai J Jonas -- A Social Ecological Perspective on Risk and Resilience for Children and Political Violence / E Mark Cummings, Laura K Taylor, Christine E Merrilees -- Everyday Helping and Responses to Crises / Allen M Omoto, Mark Snyder, Justin D Hackett -- Collective Action as Civic Engagement / Martijn van Zomeren, Tom Postmes, Russell Spears -- Intergroup Relations in Post-Conflict Contexts / John F Dovidio, Samuel L Gaertner, Ruth K Ditlmann, Tessa V West -- Humanizing Others Without Normalizing Harm / Thomas A Morton, Matthew J Hornsey, Tom Postmes -- Application and Intervention. Social Rituals and Collective Expression of Emotion After a Collective Trauma / Bernard Rime, Patrick Kanyangara, Dario Paez, Vincent Yzerbyt -- Competitive Victimhood Among Jewish and Palestinian Israelis Reflects Differential Threats to their Identities / Nurit Shnabel, Masi Noor -- Identity, Conflict, and the Experience of Trauma / Orla T Muldoon, Robert D Lowe -- Divided by a Common Language? / Leda M Blackwood, Nick Hopkins, Stephen D Reicher -- Civil Society Responses to the HIV/AIDS Crisis / Stefan Sturmer, Birte Siem -- Opinion-Based Groups and the Restoration of Civil Society / Craig McGarty, Girish Lala, Emma Thomas -- Moral Courage Training Programs as a Means of Overcoming Societal Crises / Veronika Brandst̃tter, Kai J Jonas -- Media as an Instrument for Reconstructing Communities Following Conflict / Elizabeth Levy Paluck.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Civil society; Civil society -- Psychological aspects; PSYCHOLOGY -- Social Psychology; Electronic books